Juridical Study of Resolution of Land Ownership Conflicts In The Development of Legal Security In Indonesia - Saputra, Dedi; Suprapto, Suprapto; Satriawan, Devi (Dinasti Research, 2024)
Conflicts over land ownership rights occur because of the existence of two different legal systems, namely the western legal system used by the Dutch and customary law such as customary law which is still applied in Indonesia. As a result, documents that are still under control based on the legal system, for example girik documents, SKT, stakes and so on, make legal certainty unclear. Certainty of land ownership rights in Indonesia is currently regulated based on UUPA no. 5 of 1960 in the form of a certificate document as proof of strong land control which contains physical data and juridical data as proof of land ownership rights. The best solution to resolve land ownership conflicts is to register ownership rights to land obtained based on the Dutch legal and customary system in accordance with UUPA no. 5 of 1960 and PP no. 24 of 1997 concerning land registration in conjunction with PP No. 18 of 2021 concerning management rights, land rights, apartment units, and land registration in conjunction with jurisprudence No. 234 K/Pdt/1992.